Combination and QCD analysis of charm production cross section measurements in deep-inelastic ep scattering at HERA - Abramowicz, Halina; Bunyatyan, A.; Dodonov, V.; Hennekemper, Eva; Herbst, Michael Clemens; Huber, Florian; Jung, A. W.; Lendermann, Victor; Pirumov, Hayk; Povh, Bogdan; Sauter, Michel David; Schöning, André; et al. (The European physical journal. C, Particles and fields, 2013)
Measurements of open charm production cross sections in deep-inelastic ep scattering at HERA from the H1 and ZEUS Collaborations are combined. Reduced cross sections σcc̄red for charm production are obtained in the kinematic range of photon virtuality 2.5≤Q2≤2000 GeV2 and Bjorken scaling variable 3⋅10−5≤x≤5⋅10−2. The combination method accounts for the correlations of the systematic uncertainties among the different data sets. The combined charm data together with the combined inclusive deep-inelastic scattering cross sections from HERA are used as input for a detailed NLO QCD analysis to study the influence of different heavy flavour schemes on the parton distribution functions. The optimal values of the charm mass as a parameter in these different schemes are obtained. The implications on the NLO predictions for W± and Z production cross sections at the LHC are investigated. Using the fixed flavour number scheme, the running mass of the charm quark is determined.